Euphorbia milii and propolis combination tea reduced hepatic steatosis and hepatocyte apoptosis in high-fat diet rat model - Linawati, Ni Made; Sundari, Luh Putu Ratna; Widarta, I Wayan Rai; Arijana, I Gusti Kamasan Nyoman; Wande, I Nyoman; Luvianto, Juven (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Dyslipidemia can cause various organ disorders, such as fatty liver disease. Over time, fatty liver disease has become more commonplace worldwide and may cause mortality if the progression worsens. Natural components from Euphorbia milii (E. milii) and propolis (EMP) have been demonstrated as immunomodulators that reduce total cholesterol levels.Objective: To prove the effect of EMP tea on inhibiting fatty liver and hepatocyte apoptosis in high-fat diet (HFD)-induced rats.Methods: This study applied a post-test-only control group design using 18 Wistar rats, which were divided into three groups: K0 (received standard feed), KN (received HFD of 2 g/200 g Body weight (BW) in a day), and P (received HFD of 2 g/200 g BW in a day and EMP of tea 40 mg/100 g BW in a day). The interventions were conducted for 30 days, followed by termination on day 31 for liver tissue collection and analysis. We calculated the hepatic steatosis with the help of hematoxylin-eosin (HE) staining. Hepatocyte apoptosis was also determined with terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining.Results: The K0 group had a lower hepatic steatosis percentage (17.87 ± 1.81) than KN (63.75 ± 15.88). We also found no hepatocyte apoptosis in the K0 but a high hepatocyte apoptosis index in the KN (3.98 ± 0.29). The combination of EMP tea in HFD-induced rats significantly reduced hepatic steatosis and apoptosis percentage (25.33 ± 1.17 and 0.91 ± 0.61, respectively). Conclusion: We demonstrated that combining EMP tea reduced hepatic steatosis and hepatocyte apoptotic index in HFD-induced rats, suggesting its potential as a treatment for these conditions.